Analysis of Value Added Comparison of Characteristics of Millet Flour (Setaria italica) of Selayar and Enrekang Local Varieties - Rahmah, Nur; Hidayat, Annisa Aulia Ramadhani (Agricultural Technology Education Study Program, 2023)
Food diversification by utilizing millet flour (Setaria italica) will provide added value that can significantly increase the economic value of various types of food made from millet flour. Therefore this research was conducted to compare the characteristics of the local varieties of Selayar and Enrekang millet flour and to calculate the added value ratio of millet flour. The research method is proximate testing including moisture content, protein content, and ash content; and value added analysis. The results showed that there were characteristic differences between the local varieties of Selayar and Enrekang millet flour. The results of the Selayar local variety millet flour test: Enrekang were 5.04% : 4.85% moisture content; protein content 17.31% : 15.42%; and ash content 10.37 : 8.94%; and the analysis results of added value of millet flour amounting to Rp.32,358/kg of raw material. The conclusion from the research results is that the Selayar variety millet flour has superior nutritional value, namely protein, moisture content, and ash content compared to Enrekang variety barley flour; and millet flour processing has a large added value of zero (32,358)> 0) so that it provides positive added value.